THE EFFECT OF PROVIDING REPRODUCTIVE HEALTH EDUCATION ON THE KNOWLEDGE AND ATTITUDES OF ADOLESCENT GIRLS AT NU DONOMULYO VOCATIONAL SCHOOL - Nicken Dyah Wulandari; Sulistiyah (Journal of Public Health Science, 2026)
Adolescence is a crucial stage in reproductive health development, characterized by physical, psychological, and social changes. Inadequate knowledge and attitudes regarding reproductive health may increase adolescents' vulnerability to risky behaviors. This study aimed to determine the effect of reproductive health education delivered through video media on the knowledge and attitudes of adolescent girls at SMK NU Donomulyo. This quantitative study employed a pre-experimental one-group pretest–posttest design. A total of 30 adolescent girls were selected using purposive sampling. Data were collected using validated knowledge and attitude questionnaires administered before and after the intervention. The intervention consisted of reproductive health education delivered through educational videos via a WhatsApp group. Data were analyzed using the Paired Sample t-test. The results showed that participants' knowledge improved from predominantly poor (66.7%) before the intervention to predominantly good (80.0%) after the intervention, while attitudes improved from predominantly sufficient (66.7%) to good (96.7%). The Paired Sample t-test demonstrated significant improvements in both knowledge (mean difference = -1.500; t = -7.644; p < 0.001) and attitude (mean difference = -11.400; t = -9.630; p < 0.001) following the intervention. These findings indicate that reproductive health education delivered through video media is effective in improving knowledge and fostering positive attitudes among adolescent girls. Therefore, educational video media can be considered an effective and engaging approach for adolescent reproductive health education.